Maths 2000: topics workbook 2a - Domoney, Bill (Thomas Nelson Walton-on Thames, 1995)
The core work in maths 2000 at Key Stage 1 is presented in the full colour workbooks. The books contain a wide variety of learning experiences which focus on practical work as well as formal recording activities.